Pengaruh Senam Wai Tan Kung Terhadap Keseimbangan Pada Lansia - Kusma, Nila, Isnaini Herawati , S.Fis., M.Sc (2016)
Background: Wai Tan Kung exercise is categorized as aerobic exercise and consist of slight and continuous movements followed by the withdrawal and exhalation of breath regularly. Besides, the movements in Wai Tan Kung exercise contained gymnastic movements that focus on muscle strength and balance controls in which will affect the increased ability of the respiratory muscles, and the increase the ability of the balance organs. Research Objective: This research was done to determine the effect of Wai Tan Kung exercises to the increase of balance in the elderly Research Method: This research is a Quasi Experimental of One Group Pre and Post Test method without Control Design. This research applied one group of research subjects, without using control group to determine the increase of balance in the elderly before and after Wai Tan Kung exercise. The examination of the balance was done by using "Timed up and go test" (Tug test). Results: The results obtained from the statistic test of Wilcoxon Signed Rank Test, show the value of (Asymp. Sig 2 tailed) is 0,001 which is less than the critical limit of 0.05 (sig 0.001 <0.05), therefore, H1 is accepted, that there is a significant difference between the groups pre-test and post-test. Conclusion: There is a significant effect of Wai Tan Kung exercise toward the increase of balance in the elderly.